Cash Flow Sensitivity of Cash: A Cross Country Analysis - Quader, Syed Manzur; Abdullah, Mohammad Nayeem (International Journal of Economics and Financial Issues, 2016)
Using a large panel of 5086 firms from 7 European countries, namely Belgium, France, Germany, Italy, Netherland, Sweden and UK over the period of 1981 to 2010, we made attempt to see the effect of financial constraints on international corporate policies based on their liquidity demand. Controlling for firm size, investment opportunities and alternative sources and competing uses of funds, a firm's decision to change its cash holdings is found to be positively and significantly related with internal cash flows. Our results further reveal that constrained firms like to save relatively more cash out of their cash inflows, whereas the unconstrained firms do not maintain any such significant cash hoarding behavior. The observed relationships prevail for the whole sample, within each countries and remain consistent across different estimation procedures and alternative financial constraint criteria. Our results thus point to the fact that average firms in our sample face constrained access to external finance due to financially imperfect and incomplete markets. Keywords: Asymmetric information, financial constraints, cash hoarding. JEL classifications: C26, D92, G14, L21